Predatory Journals and Afghan University Instructors; The Extent of Usage, Factors and Impact- Acknowledging Authors to Manage Their Publication Process - ADIB, Abdul Rahman; Hakimi, Abdul Aziz (Integrated Journal for Research in Arts and Humanities, 2024)
Purpose: As specialists having seen that a large number of Afghan authors throw their hard work and efforts into a trash along with an exuberant amount of their money, we conducted this study to find the root causes of predatory publishing among Afghan university instructors. Methodology: looking at the type of research problem we adopted survey design. We administered a Google Forms survey questionnaire containing both close and open ended questions to which 230 Afghan university instructors responded. Findings: The results demonstrated that a large number of Afghan university teachers get published in predatory journals for several reasons. These instructors (2.83) heavily relied on their guide teachers’ and colleagues, thus made publications based on their order or recommendation. Others (3.4) had no idea how to spot or what to do to identify predatory journals. Among them some (3.17) were either pushed or compelled themselves to publish perpetually. A number of theses teachers (3.39) knew not about predatory publishing, especially new recruited ones. Others (3.52) found it difficult to distinguish between authentic and predatory journals and a small number of them (3.65) could not afford the publication fees required by high standard, reputable journals. Theoretical framework: As indicated we first identified themes and then conducted survey to find evidence for accepting or rejecting them. The existing theories were further explored through the study. Implications: the study opens the gate for further studies and actions needed by practitioners especially calling on officials at the Ministry of Higher Education of Afghanistan to prevent predatory publishing. Value: Not only will this paper inform policy makers and practitioners to take steps but will also help authors get aware that a work can be invalid and be cautious. Limitations: This study only provides the extent, impact and reasons of predatory publishing by Afghan authors and beware them of the danger. Therefore, further study, in particular, action study is needed in their own language to help them be able to manage their scholarly publications.